HIV infection, bone metabolism, and fractures. - Güerri-Fernández, R; Villar-García, J; Díez-Pérez, A; Prieto-Alhambra, D (Sociedade Brasileira de Endocrinologia e Metabologia, 2014)
With the advent of high active antiretroviral therapy there was a significant improvement on HIV subjects survival. Thus, bone changes related to HIV became an important aspect of these individuals. HIV affects bone remodeling causing bone fragility. In addition, antiretroviral therapy may also negatively affect bone metabolism. Several studies describe an increased incidence of fractures in these patients when compared with controls without the disease. The European Society of AIDS (EACS), and other societies, have included guidance on management of osteoporosis in HIV-infected patients emphasizing the identification of patients with low bone mass. Supplementation of calcium and vitamin D and the use of alendronate in these individuals should be recommended on a case base.